Hubungan Kompetensi Pedagogik Tutor dengan Motivasi Belajar Siswa Kelas Basic di LKP Aster Pare - Urane, Muhammad Riswan; Siswanto, Heru (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
In the field of education, the instructor (or tutor) has a significant impact. He or she is in charge of carrying out educational administration at the school, which is in charge of ensuring that instruction goes smoothly. Academic credentials, proficiencies, tutor certifications, physical and emotional well-being, and the capacity to fulfill national education objectives are all requirements for tutors. ways for gathering data while making observations (questionnaires, surveys, and recordkeeping). This study employs a quantitative approach using the product moment analysis method. The correlation value between the two research variables, according to the results, was 0.713. Ha is acceptable in the product moment correlation table above if rcount> rtable, or 0.713>0.361. Thus, it can be said that basic class students at LKP ASTER English Village Pare Kediri have a positive, substantial, and unidirectional link between their enthusiasm to study English and the pedagogical ability of their tutors.